FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMANFAATAN PELAYANAN KESEHATAN DI PUSKESMAS (LITERATUR REVIEW) - Dewi Triana (Sekolah Tinggi Ilmu Kesehatan Indonesia Jaya Palu, 2024)
Introduction: Quality health services are one measure of satisfaction which will impact the patient's desire to return for treatment to an institution that provides effective services. Utilization of health services in Indonesia can generally be said to be good, but there are still several areas that experience problems in utiliz-ing health services. The factors that influence the use of health services are predisposing characteristics which include demographic characteristics (gender, age), social (level of education, occupation, ethnicity/race) and beliefs about health (attitudes, perceptions). Supporting characteristics include family capabilities. Method: The method in this research is the literature study method. This research uses a literature review, by collecting articles from research on PubMed and Google Scholar. By using keywords utilization of health services at community health centers. The criteria for research articles are articles published between 2020-2023 in na-tional journals. Results: Factors that were correlated with the use of health services in this study were health workers (nurses and midwives), accessibility, knowledge, attitudes and history of illness. Quality of service, Conclusion: There is a relationship between illness history, knowledge, attitudes, perceptions of health condi-tions and information on the utilization of nursing services at the Community Health Center.